KDYMM SPB YDP Agong awards Proclamation Certificates for Pro-Chancellor and UMPSA - Mimi Rabita, Abd Wahit (UMPSA, 2023)
GAMBANG, 21 October 2023 - His Majesty the Yang di-Pertuan Agong Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Almarhum Sultan Haji Ahmad Shah Al-Musta’in Billah, Tuanku Chancellor of UMPSA set out to complete the Investiture of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and the awarding of the UMPSA Pro-Chancellor’s proclamation certificate to the Regent of Pahang, Tengku Mahkota Tengku Hassanal Ibrahim Alam Shah Ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah in conjunction with the 18th UMPSA Convocation Ceremony today.